Active control of wind induced responses using plasma actuators - Shrestha, Saugat; Pennung Warnitchai; Anwar, Naveed; Punchet Thammarak; Suvit Punnachaiya; Phongphaeth Pengvanich; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Plasma actuators has been a new technology used for the flow control in the field of aerodynamics. However, the research has not been carried out in the field of structural engineering. So, Plasma actuator has been applied with the view of control for civil engineering structures. So, the project is the blend of the electrical and structural engineering. Initially, plasma actuator driver circuit is prepared meeting the requirements of high voltage and high frequency. The output from the driver is applied to a dielectric barrier discharge actuator prepared with copper electrodes in either side of the dielectric barrier. Due to the ionization of air plasma is generated along with electric wind (due to the electric wind). Electric wind is a significant major parameter to for the flow control. So, the actuators are optimized to attain the maximum possible electric wind for the aerodynamic response control. These actuators are applied to the basic bluff body shapes, square and circle at different strategic locations. These models are tested in the wind tunnels at different wind speeds. High Frequency Pressure Integration test is carried out in the wind tunnel. The mean and the fluctuating components of the aerodynamic forces is analyzed. The effect of plasma actuation is definitive from the analysis. Smoke test is also carried out to provide further qualitative evidence to the effectiveness of plasma actuation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Actuators; Wind-pressure; Structural dynamics